INTERACTION DESIGN FOR INTERACTIVE LEARNING IN MOOCS USING USER-CENTERED DESIGN APPROACH - Austin Stefano, Kevin
Education is the key to progress the development of a nation because the great nation must have a strong educational foundation. However, the poor quality of education becomes the obstacle that often occurs. The quality of education is influenced by the interaction of communication in the learning process. Therefore, the interactive learning method could be the solution to improve the quality of interaction and communication in the learning process. Even more, interactive learning could improve the learning gain and conceptual understanding through the interaction of students in the learning process. However, several challenges are faced in the learning process due to the pandemic. Interaction in the learning is limited to break the chain of COVID-19 transmission. The learning model has to be adaptive during the pandemic to improve its continuity through online learning. Therefore, MOOCs (Massive Open Online Courses) could be the answer to offer the course for the learning process in an organized and structured online classroom environment. Based on the user research, we analyze the user needs and requirements to implement interactive learning methods, discussion and think-pairshare using user-centered design approach in ISO 9241-210:2010. The final result of this final project is an interaction design, in the form of a high-fidelity prototype. The test results through usability testing show that the usability goal of efficient to use has been successfully achieved with an average SEQ score of 6.96 out of 7 above the threshold of 5.5. In addition, the usability goal of effective to use and the user experience helpful in the interactive learning process has been achieved with an average SUS score of 88 out of 100 above the threshold of 68. The usability goal of effective to use has also been successfully tested with a completion rate and achieved a completion rate of 100%.